APPROACHING THE PATELLOFEMORAL PAIN SYNDROME THROUGH PHYSIOTHERAPEUTIC METHODS VERSUS KINETOTHERAPY - Dobreanu (căs. Ioja) Ioana-Bianca; Cojocariu Adrian (Sport şi Societate)
Considering the importance of the knee joint in everyday life, both for carrying out daily activities and for carrying out professional activities, we can conclude that its recovery is extremely important.The production mechanisms of the femoro-patellar syndrome are multiple, and this requires the implementation of a recovery program as effective as possible, based on the most accurate and detailed assessment.Regarding the modification of the activity, we are left with a series of contraindications such as; avoiding deep bending of the knee against resistance. Maintaining an adequate body mass index should be part of any anterior knee pain management program. Muscle toning exercises are recommended without crossing the painful threshold, performed especially in a closed kinetic chain, and hydrotherapy offers numerous benefits in performing movements by reducing joint stress.As far as physiotherapy methods are concerned, they can be considered very important in reducing pain in patients with femoro-patellarsyndrome, because with their help we can implement the kinetotherapeutic exercise program early and without the presence of pain.In the present paper, two of the most frequently applied protocols for patients diagnosed with femoral-patellar syndrome weretested on 2 different groups of patients. Although the results are beneficial for patients through the prism of both programs, we can still state that the simultaneous use of kinesiotherapy together with physiotherapy could provide promising results for patients diagnosed with this syndrome.